2022
DOI: 10.1016/j.radcr.2022.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of a giant pyonephrosis: A case report

Abstract: Pyonephrosis is a suppurative infection of the kidney caused by ureteral obstruction. It can lead to kidney failure, septic shock, and death. Thus, it requires prompt assessment and appropriate management. We report a case of a 63-year-old male with giant pyonephrosis contained 10 liters of pus and spontaneously ruptured in the adjacent muscles. This clinical case illustrates the value of computed tomography scan in the diagnosis and management of an uncommon upper urinary tract infection and its complications. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“… 9 Niang et al recently reported a case of giant pyonephrosis containing 10 liters of pus and spontaneously ruptured in the adjacent muscles and the treatment was an aspiration followed by a nephrectomy by laparotomy. 10 In our case, we initially managed her with percutaneous drainage of pus and stabilized with hydration and intravenous antibiotics, followed by simple nephrectomy on an elective basis. The patient had an uneventful postoperative course and follow up.…”
Section: Discussionmentioning
confidence: 91%
“… 9 Niang et al recently reported a case of giant pyonephrosis containing 10 liters of pus and spontaneously ruptured in the adjacent muscles and the treatment was an aspiration followed by a nephrectomy by laparotomy. 10 In our case, we initially managed her with percutaneous drainage of pus and stabilized with hydration and intravenous antibiotics, followed by simple nephrectomy on an elective basis. The patient had an uneventful postoperative course and follow up.…”
Section: Discussionmentioning
confidence: 91%
“…Calcium and uric stones are usually noninfectious and result from an imbalance between factors that promote or inhibit urine crystallization [ 10 ]. In patients with these types of calculi, infection may occur secondarily after long-standing obstruction, leading to bacterial overgrowth associated with urinary stasis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although rupture of pyonephrosis is also very rare, Niang et al recently reported a retroperitoneal rupture with extension up to the crural muscles, treated successfully by percutaneous nephrostomy followed by nephrectomy [ 12 ]. Intraperitoneal ruptures are also possible.…”
Section: Discussionmentioning
confidence: 99%